Electrical and dielectric properties of kevlar - carbon hybrid fiber / epoxy laminated composites (Baghdad Science Journal, 2025)
This paper reports a.c., d.c. conductivity and dielectric behavior of Ep-hybrid composite with12 Vol.% Kevlar-Carbon hybrid . D.C. conductivity measurements are conducted on the graded composites by using an electrometer over the temperature range from (293-413) K. It was shown then that conductivity increases by increasing number of Kevlar –Carbon fiber layers (Ep1, Ep2, Ep3), due to the high electrical conductivity of Carbon fiber. To identify the mechanism governing the conduction, the activation energies at low temperature region (LTR) and at high temperature region (HTR) have been calculated. The activation energy values for hybrid composite decrease with increasing number of fiber layers. The a.c. conductivity was measured over frequency range 100 Hz-1MHz. It was found that? ?(?) values increase with increasing frequency according to the relation ? (?)=Aws . The values of frequency exponent (s) were found to increase with number of layers.